2017
DOI: 10.3389/fnagi.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Neuroplasticity in Response to Physical Activity in Old Age: The Case for Dancing

Abstract: From animal research, it is known that combining physical activity with sensory enrichment has stronger and longer-lasting effects on the brain than either treatment alone. For humans dancing has been suggested to be analogous to such combined training. Here we assessed whether a newly designed dance training program that stresses the constant learning of new movement patterns is superior in terms of neuroplasticity to conventional fitness activities with repetitive exercises and whether extending the training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 42 publications
8
128
0
5
Order By: Relevance
“…The cognitive development and BDNF changes are highlighted in our recent report (see Müller et al, 2017). The intervention was provided for 18 months and contained three time-points of measurement: baseline pre-test, first post-test after 6 months of training and second post-test after 18 months of training (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 81%
“…The cognitive development and BDNF changes are highlighted in our recent report (see Müller et al, 2017). The intervention was provided for 18 months and contained three time-points of measurement: baseline pre-test, first post-test after 6 months of training and second post-test after 18 months of training (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 81%
“…Although an increase in hippocampal volume was reported after both aerobic [24] and resistance training in older adults [130], few brain imaging studies are currently available that directly compare different types of physical training. For instance, it was observed that dancing conducted for several months led to a greater increase in cortical grey matter in frontal and temporal regions [298][299][300] and in hippocampal volumes [301] than a combination of resistance, endurance, and flexibility training. Hence, comparing different types of physical interventions (e.g., resistance training vs. aerobic training vs. dancing) with regard to their effectiveness in evoking structural and functional brain changes is an interesting topic for further studies.…”
Section: Structural Brain Changes and Cognition In Response To Resistmentioning
confidence: 99%
“…The study results revealed no increase in brain volume after exergame training. However, previous animal and human studies showed structural brain alternations after a variety of physical exercises in gray and white matter; for example after aerobic training (13,24,128,129), after strength training (15), after coordinative exercises (130)(131)(132)(133)(134), after dancing (111,121,135) or after Tai Chi (136). Moreover, changes in brain structure have been reported after cognitive training (29)(30)(31)(32)(33)137).…”
Section: Structural Plasticity Effectsmentioning
confidence: 99%